Stunting Prevention in Pregnant Women: Evaluation of the Supplementary Feeding Program in Rahayu Village, Soko District, Tuban Regency - Nurul Jariyatin; Amarullah; Sony Aditya Kusuma; Zuhryansah (LPPM ISTeK ICsada Bojonegoro, 2025)
Stunting in children is a serious public health problem, which is influenced by various factors, including lack of nutritional intake in pregnant women. The supplementary feeding program (PMT) is one strategy to prevent stunting in children. In this program, we collaborate with Pertamina EP and ISTek ICsada Bojonegtoro. This study aims to evaluate the implementation of the supplementary feeding program for pregnant women in Rahayu Village, Soko District, Tuban Regency, in an effort to prevent stunting. This research method uses a qualitative approach with a descriptive study design. Data were collected through interviews with pregnant women who received PMT. The results of the study showed that after the PMT program was implemented, the nutritional intake of pregnant women had increased, however, there were still obstacles in terms of monitoring the sustainability of consumption and family involvement. This Pregnant Women Class was attended by 20-30 Pregnant Women Participants from 3 Villages (Rahayu Village, Bulurejo Village, Kebonagong Village). This study suggests that the program of pregnant women's classes with the provision of PMT should continue to run every month, in order to further optimize stunting prevention in 2025.